1990
DOI: 10.1093/oxfordjournals.aje.a115579
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Diarrhea During the First Year of Life Associated With Initial and Subsequent Colonization by Specific Enteropathogens

Abstract: The incidence of colonization by enteropathogenic, enterotoxigenic, enteroinvasive, and enterohemorrhagic Escherichia coli (detected by DNA hybridization with specific radiolabeled probes), Salmonella sp., Shigella sp., Campylobacter jejuni, and rotavirus was related to the presence of diarrhea in a cohort of 75 rural infants followed longitudinally during the first year of life. The study was carried out between August 1985 and February 1987 in the village of Lugar Sobre la Tierra Blanca, in the state of More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
90
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 0 publications
10
90
2
Order By: Relevance
“…We identified a prevalence of ETEC of 5.3% in children with diarrhea between 2 and 24 months of age. This prevalence rate is lower than the rates reported from other studies performed in developing countries: 38% in children Ͻ2 years of age in Nicaragua (19), 33% in children Ͻ1 year of age in Mexico (6), and 18% in children Ͻ5 years of age in Argentina (32). These differences may be related to the age of the population and the type of study (passive versus active surveillance and a community-based versus hospital-based study).…”
Section: Discussioncontrasting
confidence: 66%
“…We identified a prevalence of ETEC of 5.3% in children with diarrhea between 2 and 24 months of age. This prevalence rate is lower than the rates reported from other studies performed in developing countries: 38% in children Ͻ2 years of age in Nicaragua (19), 33% in children Ͻ1 year of age in Mexico (6), and 18% in children Ͻ5 years of age in Argentina (32). These differences may be related to the age of the population and the type of study (passive versus active surveillance and a community-based versus hospital-based study).…”
Section: Discussioncontrasting
confidence: 66%
“…[10][11][12][13][14][15][16] Acquired immunity from frequent previous exposures, longterm convalescent shedding of the organism, or exposure to insufficient amounts of an organism to cause disease are the main explanations for asymptomatic carriers. 15,[17][18][19] Several studies have reported a high prevalence of Salmonella , Giardia , and Campylobacter in children without diarrhea in developing countries. 16,20,21 Recent data from Vietnam reported 23% of diarrheagenic E. coli in both diarrhea cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Infants are more likely to develop diarrhea during the first episode of colonization with EPEC than they are during subsequent encounters (11). It is not known whether the low incidence of EPEC diarrhea in older children and adults is due to acquired immunity.…”
mentioning
confidence: 99%